Strategy, Marketing Effectiveness and Firms Performance - Erwin Saraswati; Abdul Ghofar (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
In the global era, firms should have a competitive advantage strategy, since their business environment is very competitive. Miles and Snow (1978) divide a firm’s strategy into four types, namely prospector, defender, analyzer and reaction. Prospectors and defenders are in the two extreme sides. We examine differences between marketing effectiveness of prospectors and defenders and its association with accounting performance. The sample of this research consists of 54 firms, which are 27 categorized as prospectors and 27 as categorized as defenders. Three hypotheses are examined: (1) the marketing effectiveness of prospectors is higher than defenders; (2) marketing effectiveness is associated positively and strongly with accounting performance; and (3) there is an association between strategy and accounting performance. The result of this research supports the argument that prospectors have more marketing effectiveness than defenders and the marketing effectiveness is associated with accounting performance. On the contrary, this research found the association between strategy and accounting performance does not exist.Keywords: prospector, defender, marketing effectiveness and accounting performance